Schistosoma mansoni coactivator associated arginine methyltransferase 1 (SmCARM1) effect on parasite reproduction - Coelho, Fernanda Sales; Gava, Sandra Grossi; Andrade, Luiza Freire; Geraldo, Juliana Assis; Tavares, Naiara Clemente; Lunkes, Felipe Miguel Nery; Neves, Renata Heisler; Machado-Silva, José Roberto; Pierce, Raymond J.; Oliveira, Guilherme; Mourão, Marina Moraes (Frontiers in Microbiology, 2023)
The human blood fluke parasite Schistosoma mansoni relies on diverse mechanisms to adapt to its diverse environments and hosts. Epigenetic mechanisms play a central role in gene expression regulation, culminating in such adaptations. Protein arginine methyltransferases (PRMTs) promote posttranslational modifications, modulating the function of histones and non-histone targets. The coactivator-associated arginine methyltransferase 1 (CARM1/PRMT4) is one of the S.mansoni proteins with the PRMT-core domain. We carried out in silico analyses to verify the expression of SmPRMTs in public datasets from different infection stages, single-sex versus mixed-worms, and cell types. The SmCARM1 function was evaluated by RNA interference. Gene expression levels were assessed, and phenotypic alterations were analyzed in vitro, in vivo, and ex vivo. The scRNAseq data showed that SmPRMTs expression is not enriched in any cell cluster in adult worms or schistosomula, except for Smcarm1 expression which is enriched in clusters of ambiguous cells, and Smprmt1 in NDF+neurons and stem/germinal cells from schistosomula. Smprmt1 is also enriched in S1 and late female germ cells from adult worms. After dsRNA exposure in vitro, we observed a Smcarm1 knockdown in schistosomula and adult worms, 83% and 69%, respectively. Smcarm1-knockdown resulted in reduced oviposition and no significant changes in the schistosomula or adult worm phenotypes. In vivo analysis after murine infection with Smcarm1-knocked-down schistosomula, showed no significant change in the number of worms recovered from mice, however, a significant reduction in the number of eggs recovered was detected. The ex vivo worms presented a significant decrease in the ovary area with a lower degree of cell differentiation, vitelline glands cell disorganization, and a decrease in the testicular lobe area. The worm tegument presented a lower number of tubercles, and the ventral sucker of the parasites presented a damaged tegument and points of detachment from the parasite body. This work brings the first functional characterization of SmCARM1 shedding light on its roles in S.mansoni biology and its potential as a drug target. Additional studies are necessary to investigate whether the reported effects of Smcarm1 knockdown are a consequence of the SmCARM1-mediated methylation of histone tails involved in DNA packaging or other non-histone proteins.